Management of the Open Abdomen - Mericli, Alexander F. (Seminars in Plastic Surgery, 2018)
Management of the abdominal catastrophe requires a multidisciplinary approach. The plastic surgeon is a key member of the surgical team assisting in the creation of a durable, functional anatomic abdominal wall reconstruction. Plastic surgeons must be familiar with the concepts and pathophysiology related to the open abdomen, techniques for temporary abdominal closure, and when such techniques are appropriate to implement. In this article, the authors provide a review of the open abdomen concept, which practicing plastic surgeons and trainees may find helpful if faced with this clinical scenario.
Keywords: open abdomen; ventral hernia; damage control; abdominal wall reconstruction; component separation; mesh